The effect of sustainable investments to the economic objectives of the company in relation to the total quality management - Jochen Schmid; Marieta Olaru; Ana-Maria Verjel (Amfiteatru Economic Journal, 2017)
The implementation of the sustainability mega-trend has been increasing in large companies, listed for many years in order to respond to stakeholder`s interests. One of the objectives of the paper is to identify how the sustainable investments behaves with business objectives in terms of total quality management. This remains unclear in the given studies. The paper highlights part of the value of research based on the survey conducted on German corporations that were quoted on the DAX30 stock index during 2007-2014. Public annual reports as well as company figures from the base of this paper. As a result of the study, it appears to be difficult forming a unique interpretation of complex company structure, but there are detectable correlations between sustainable investments and economic objectives in total quality management that have been found in the research.
Keywords: M1; 330; sustainability; sustainable investments; economic objectives; total quality management (TQM); corporate social responsibility (CSR); economic value